Positioning Produk Pertanian Organik - Neng Elmi Salehah; Amalia Nur Milla; Neneng Kartika Rini (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2021)
The trend of organic agriculture is currently experiencing an increase, changes in people's lifestyle patterns have made a shift in consumption patterns from non-organic to organic. There is a process of competition in a very tight marketing world where companies or producers must be able to compete in the market, one of which is by implementing a marketing strategy through Positioning. This study aims to determine what are the factors that influence the positioning of organic agricultural products in Kebonpedes Subdistrict, Sukabumi Regency. This research uses descriptive research with explanatory methods and quantitative approaches, while the type of sampling used is snowball sampling. Based on the results and discussion of the analysis carried out in this study partially it was stated that six factors had no significant effect on the positioning of organic products in Kebonpedes District, namely quality, service, price, use, brand, benefits and one significant influence factor, namely competitors, while simultaneously quality, service, price, usage, brand, benefits and competitors have a significant together.